Intimate Partner Violence Training and Readiness to Respond among Students, Staff, and Faculty in Three Institutions in the United States - Fedina, Lisa (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is a significant public health concern; however, limited studies have explored perceptions and experiences towards IPV among students, staff, administrators, and faculty across diverse disciplines at institutions of higher education. The purposes of this study were to (1) assess experiences of IPV among a sample of students, staff/administrators, and faculty and (2) examine the relationship among attitudes, actual and perceived knowledge, awareness, training, readiness, and personal experiences with IPV in this sample. Participants were recruited from an urban university and two university-affiliated medical institutions to participate in an online survey. Bivariate and multivariate associations were assessed. Structural Equation Modeling (SEM) was used to examine direct and indirect effects of perceived and actual knowledge and personal experiences with IPV. Of the 216 respondents, 42.6% reported personally experiencing IPV and 34.3% reported having witnessed IPV. Over 34% of participants never received training on IPV. The sub-sample with training received between one and more than 15 hours of training. Standardized total effect of training on attitudes and awareness was β = 0.42 (95% confidence interval [CI] = 0.30–0.51), the combined indirect effects was β = 0.18 (95% CI = 0.10–0.27) and the direct effects of β=0.23 (95% CI = 0.12–0.34), indicating that hours of training was highly associated with the participants’ perceived knowledge and actual knowledge, which improved their attitudes and awareness towards IPV survivors. Our findings suggest the need for campus-wide formal training on IPV to better prepare members in higher education to accurately identify, assess, and intervene to protect victims of abuse. Interprofessional approaches are needed that focus on the multiple and intersecting needs of victims of violence and should also enhance professional self-efficacy and increase readiness to respond to IPV survivors.